PENYELESAIAN SENGKETA TANAH MELALUI LEMBAGA ADAT DI DESA SABUNGAN NIHUTA KECAMATAN RONGGUR NIHUTA KABUPATEN SAMOSIR - Ratna D. E Sirait; Mardongan Erik Martua Simatupang (LPPM Universitas Katolik Santo Thomas Medan, 2025)
This study aims to find out and understand the role of Customary Institutions in resolving land disputes in Sabungan Nihuta village, Ronggur Nihuta District, Samosir Regency and to find out the decisions of Customary Institutions in Sabungan Nihuta village, Ronggur Nihuta District, Samosir Regency. This study uses empirical juridical research methods and data in this study are primary data and secondary data. Primary data in the form of data obtained directly from the results of interviews with Mr. Osmar Simbolon, the king of drugs in Sabungan Nihuta, and Mr. Osben Simalango who is also the secretary of Sabungan Nihuta village. Secondary data is obtained through documentation studies, by searching for data from various scientific books, laws related to the problems discussed. The data is then analyzed and formulated as supporting material in the writing of the thesis to be compiled. The results of this study show that the role of Customary Institutions in resolving land disputes in Sabungan Nihuta village, Ronggur Nihuta District, Samosir Regency plays a major role in resolving land disputes because of the high trust of the community in customary institutions in handling conflicts and disputes, knowing more about the origin of land and every land ownership in Sabungan Nihuta. As well as being a forum for deliberation for the Sabungan Nihuta community in the event of a dispute because customary institutions focus on restoring social relations. The decision from the results of the deliberations (Marria) of the Bius Sitolu Hae Horbo Sabungan Nihuta customary institution is still recognized and implemented and considered as customary law by the people of Sabungan Nihuta village, Ronggur Nihuta District, Samosir Regency.